Problem Pengelolaan Madrasah Aliyah dan Solusinya - Nur Ahid (Islamica: Jurnal Studi Keislaman, 2010)
Many High Schools (Aliyah) in Indonesia are faced with one of the following problems: low operational expenditure, poor human resources, unsettled contract with the teachers, small number of the teachers, and poor facilities. This paper tries to speak of the practical ways to come to terms with such problems. These practical ways -some of which are related to money- are in fact ideals. These ideals in one way or another are the foundations for the practical problems that our schools face. By ideals we mean such values as determination, discipline, and right vision for the school. The paper argues that money is not a magic stick that may solve all problems. he key is that all elements of school must use the best they have to realize the best they want to achieve. Practical problems may be solved by ideals, obsessions and dreams. In a country where money is rare, the vision and orientation of our education should change the character of the educated from being money-oriented to ideals-oriented.